Pengaruh Mekanisme Corporate Governance Terhadap Manajemen Laba - Brenda Prasasti; Jimmy Ardianto (Universitas Multimedia Nusantara, 2011)
The objective of the empirical study is to examines whether corporate governance mechanism which consists of institutional ownership, managerial ownership, size of director to earnings management, and presence of independent of director had an influence on earnings management. Earnings management is proxied by discretionary accruals that are estimated using Jones model. This study takes sample from 47 companies listed in Indeks Kompas 100 has been reviewed during the year of 2008-2009. Double linier regression analysis is used to analyze the effect of corporate governance mechanism on earnings management. The result on this study shows that (1) Simultaneously of corporate governance mechanism which consists of institutional ownership, managerial ownership, size of director to earnings management, and presence of independent of director had significant influence on earnings management, (2) Institutional ownership had not significant inffluence on earnings management, (3) Manajerial ownership had positive significant influence onearnings management, (4) Size of director had not significant inffulence on earnings management, (5) Presence of independent of director had not significant influence on earnings management. Keywords : Corporate Governance Mechanism, Earnings Management